Academic capitalism and academic culture: A case study. - Mendoza, Pilar; Berger, Joseph B. (Education Policy Analysis Archives, 2008)
This case study investigated the impact of academic capitalism on academic culture by examining the perspectives of faculty members in an American academic department with significant industrial funding. The results of this study indicate that faculty members believe that the broad integrity of the academic culture remains unaffected in this department and they consider industrial sponsorship as a highly effective vehicle for enhancing the quality of education of students and pursuing their scientific interests. This study provides valuable insights to federal and institutional policiescreated to foster industry-academia partnerships and commercialization of academic research.